Efektivitas Daun Katuk Terhadap Kecukupan Air Susu Ibu (ASI) Pada Ibu Menyusui Di Bidan Misniarti Tahun 2023 - Lasria Yolivia Aruan; Yasrida Nadeak; Dessy Ratna Sari (Jurnal Anestesi, 2023)
Introduction: Exclusive breastfeeding is a global strategy to improve the growth, development, health and survival of babies. One effort to increase breast milk supply is by improving the quality of food which has a direct effect on milk production, namely katuk leaves. Objective: aims to determine the effect of katuk leaf extract on the adequacy of breast milk production in post partum mothers at Midwife Misniarti. Method: This research is a quasi experiment with a two group posttest only design. This research method is a quasi-experimental design with a nonequivalent control group design. The sample in this study was 30 people consisting of 15 experimental groups and 15 control groups. Data collection uses an observation sheet. Univariate analysis uses central tendency distribution and bivariate analysis uses paired t test. The results showed that the mean sufficiency of breast milk in the experimental group before giving katuk leaves was 6.80 and after giving katuk leaves was 8.47. The conclusion is that giving katuk leaves has proven to be effective for the adequacy of breast milk (ASI) in breastfeeding mothers.